Land use change analysis using NDVI approachment in Terbanggi Besar, Central Lampung at 2000 and 2020 (Applied Research in Science and Technology, 2021)
Terbanggi Besar is one of the Subdistricts in Central Lampung Regency, which has an area of 217.15 km2. The large area of land is used as a settlement and also used to cultivate crops. Each year, the population in this Subdistrict keeps increasing; this becomes a problem since the increasing population means the need for the living area also increases. This affects is the cultivation area by turning it into a residential area. The research aims to analyze land use changes based on vegetation density in the Terbanggi Besar sub-Subdistrict in 2000 and 2020. The data from the respective Landsat 7 and 8 satellite images using multi-temporal dimensions using Geographical Information Systems (GIS) through the Argis application and Landsat imagery with the NDVI method. The results indicate that land use dynamics in the Terbanggi Besar Subdistrict have fluctuated in the last 20 years. The largest land use in Terbanggi Besar Subdistrict in the period 2000 to 2020 is medium density vegetation with an area of 21,465 hectares, low-density vegetation 17,453 hectares, and open land 2,624 hectares.